128. Antibiotic Prophylaxis Prior to Dental Visits in the Veterans Health Administration (VHA), 2015–2018. (31st December 2020) - Suda, Katie J; Fitzpatrick, Margaret A; Poggensee, Linda; Echevarria, Kelly; Hubbard, Colin; McGregor, Jessina C; Evans, Charlesnika T
Abstract: Background: Antibiotic prophylaxis (AP) is recommended prior to invasive dental visits in patients with certain cardiac conditions but is not recommended in patients with prosthetic joints. Meta-analyses indicate benefit of AP prior to dental implants and tooth extractions. Within dentistry, it is also common to prescribe AP in patients with immunocompromising conditions. Our objective was to determine appropriateness of AP by VHA dentists. Methods: A national cross-sectional study of dental visits was conducted in VHA, 2015–2018. Antibiotics prescribed 7 days before a visit were included. Antibiotics prescribed for an oral infection were excluded (15%). Appropriate AP was defined as visits with gingival manipulation and was further delineated into narrow and broad definitions by medical comorbidities. The narrow definition (primary analysis) only included cardiac conditions at risk of infective endocarditis. The broad definition included these cardiac conditions, tooth extractions/implants or immunocompromising conditions. The association of covariates with unnecessary AP was modeled using GEE for logistic regression. Results: Out of 367, 872 patient-visit dates associated with an antibiotic, 85% were prescribed for AP (N=313, 886 prescriptions; median=7 days). AP (74% amoxicillin, 18% clindamycin) was prescribed to 198, 314 patients (91% male; mean age=62 years). 87% of dental visits were categorized as gingival manipulation. With the narrow definition (cardiac only), 15% of AP were guideline concordant, increasing to 73% with the broader definition (cardiac or implant/extractions or immunocompromised). For the narrow definition, Black or other non-white race, current smoking, penicillin allergy and visits located in the West or South were associated with unnecessary AP. Protective factors were older age, prosthetic joints, immunocompromised, dental implants, extractions and visits in the Midwest. Unnecessary AP increased over time. Conclusion: Few antibiotics prescribed before dental visits were for oral infections. Focusing on improving AP duration and appropriateness may have large implications for stewardship. Guidelines should inform if AP is indicated for extractions, implants, and immunocompromised patients. Disclosures: All Authors : No reported disclosures